Immunogenicity and safety of a single dose of a live attenuated Japanese encephalitis chimeric virus vaccine in Vietnam: A single-arm, single-center study. (January 2018) - Vu, Thiem Dinh; Nguyen, Quang Dang; Tran, Huong Thi Ai; Bosch-Castells, Valérie; Zocchetti, Céline; Houillon, Guy
Highlights: JE-CV is a live attenuated chimeric vaccine against Japanese encephalitis. It elicited a protective immune response in those aged 9 months–60 years in Vietnam. By Day 28, 98.5% of participants in the per protocol analysis had seroconverted. The vaccine was well tolerated, with no safety concerns. These results are consistent with those reported in other endemic countries. Abstract: Objective: To describe the immunogenicity and safety of the Japanese encephalitis chimeric virus vaccine (JE-CV) in children and adults in Vietnam. Methods: In this prospective, open-label, single-center, single-arm study, 250 healthy participants aged 9 months to 60 years received a single dose of JE-CV (IMOJEV ® ). JE neutralizing antibody titers were assessed at baseline and 28 days after vaccination using the 50% plaque reduction neutralization test (PRNT50 ). Safety and reactogenicity were assessed through solicited and unsolicited adverse events. Findings: Seroconversion (titer ≥10 [1/dil] in participants JE seronegative [titer <10] at baseline [per protocol analysis], or a 4-fold rise from a baseline titer ≥10) and seroprotection (titer ≥10 [1/dil]) rates 28 days after vaccination were both 98.5% (132/134) in the per protocol analysis, and 82.4% (201/244) and 98.8% (242/245), respectively, in the full analysis set. Geometric mean titers (GMTs) increased in all age groups from Day 0 to Day 28; Day 28/Day 0 GMT ratios were 55.3 (95% confidence interval [CI] 38.4–79.8), 348 (95% CI 211–572), 296 (95% CI 152–576) and 194 (95% CI 13.1–2870) in those aged 9 months to 4 years, 5–11 years, 12–17 years and 18–60 years, respectively, in the per protocol analysis. There were no safety concerns during the study. Conclusion: A single dose of JE-CV in children and adults aged 9 months to 60 years in Vietnam elicited a protective immune response and was well tolerated with no safety concerns. Registered atwww.clinicaltrials.gov (NCT02492165).